KINERJA PEREKONOMIAN KABUPATEN KAPUAS HULU PERIODE TAHUN 2009-2013 - B61109054, WISDAYANTI (Jurnal Ekonomi Daerah (JEDA), 2015)
Succes or not development in a region can be seen on the economic performance that region. The region economic performanceÂ  in certain periode can be seen on economic development and economic growth that region. Ecnomic development can not be separate from economic growth which both is interconnected to one another. Economic development push economic growth, and economic growth expediting the process of economic development. There three component which influence the economic performance, and these three component related to each other. These three component are national growth component; propotional shift or sectoral growth; and differential shift or competitivegrowth. Kapuas Hulu as one of the region in West Kalimantan Province,Â  a region which has the second largest land area after Ketapang. Large area not guarantee that region had great economic growth. Kapuas Hulu economic growth if compared with the economic growth of West Kalimantan Province, the Kapuas Hulu economic growth is below the West Kalimantan Province. This thesis aims to identity and analyze the economy position of Kapuas Hulu based tipilogi regional by using analysis tipilogi regional, determine and analyze the position of nine economic sectors and sub-sectors which based on PDRB Kapuas Hulu using analysis tipilogi sectoral, and to analyze each economic sector Kapuas Hulu using Shift Share analysis (SS). Kata Kunci : Economic Performance, Tipilogi Regional, Tipilogi Sektoral, Shift Share (SS)